The previous product of sines can be expressed in the form where and are positive integers. Find the product
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
First, we are going to state the following formula : 1 − e 2 θ i = 2 sin θ e i ( θ + 3 π / 2 ) ( ∗ )
The proof of this formula is very simple. We just have to use the fact that sin θ = 2 i e i θ − e − i θ , and the fact that e i ( 3 π / 2 ) = − i .
Now, for any natural number n and any angle θ we can define the polynomial p ( z ) = z n − e 2 n θ i , with zeros e i ( 2 θ + n 2 k π ) , where k is any integer number satisfying 0 ≤ k ≤ n − 1 . Then z n − e 2 n θ i = ∏ k = 0 n − 1 ( z − e i ( 2 θ + n 2 k π ) ) . Evaluating at z = 1 , we get 1 − e 2 n θ i = ∏ k = 0 n − 1 ( 1 − e i ( 2 θ + n 2 k π ) ) . Now we use the formula ( ∗ ) in both sides, so we get 2 sin ( n θ ) e i ( n θ + 3 π / 2 ) = k = 0 ∏ n − 1 ( 2 sin ( θ + n k π ) e i ( θ + n k π + 3 π / 2 ) ) The right side of which can be transform like this: 2 n ∗ k = 0 ∏ n − 1 sin ( θ + n k π ) k = 0 ∏ n − 1 e i ( θ + n k π + 3 π / 2 ) = 2 n ∗ e i ( n θ + 2 ( n − 1 ) π + 3 n π / 2 ) k = 0 ∏ n − 1 sin ( θ + n k π ) = = 2 n ∗ e i ( n θ + 2 n π − π / 2 ) k = 0 ∏ n − 1 sin ( θ + n k π ) = 2 n ∗ e i ( n θ − π / 2 ) k = 0 ∏ n − 1 sin ( θ + n k π ) .
Now, dividing both sides of the formula 2 sin ( n θ ) e i ( n θ + 3 π / 2 ) = 2 n ∗ e i ( n θ − π / 2 ) ∏ k = 0 n − 1 sin ( θ + n k π ) by 2 ∗ e i ( n θ − π / 2 ) sin θ , we obtain that 2 n − 1 ∏ k = 1 n − 1 sin ( θ + n k π ) = sin θ sin n θ . Making n = 1 2 7 , in this general formula, we obtain 2 1 2 6 ∏ k = 1 1 2 6 sin ( θ + 1 2 7 k π ) = sin θ sin 1 2 7 θ . Therefore A = 1 2 7 and B = 1 , and the answer is A B = 1 2 7 .